Design and deveploment of motion and thermal controller for thermal fatigue machine - Mohamad Ridhwan Shahril, Baharudin (2016)
This report presents the design and development of motion and a thermal controller for thermal fatigue machine. Automation system has become an important medium in manufacturing operation. The time required to perform a complete testing is depend on the performance of the machine control system. Thus, by designing a better controller in a system, it will improve the overall performance of the machine. In this project, the pneumatic system was used as a platform to the design of motion and thermal controller as the control console for the furnace. Then, the performance of motion and the thermal controller was evaluated. The pneumatic cylinder was used as mechanical devices by the power of compressed air to drive the reciprocating linear motion and rotary motion. The pneumatic control was performed automatically by OMRON’s Programmable Logic Controller (PLC) based on Ladder Logic Diagram. PLC has 5v to 24v I/O voltage range which is compatible with many types of sensor and solenoid. The motion of the machine was designed based on motion sequence requirement. Cascading pneumatic circuit was used as design methods to perform the motion sequence. The furnace control console was designed to have two temperature controllers. The first controller was connected to main thermocouple which was designed to measure the temperature of heating element. While, the second controller was connected to secondary thermocouple which was design to measure the temperature of molten aluminium. This project was successfully completed with all controller was able to perform the required motion and thermal control for the thermal fatigue machine.